Determination of Genotypic Factors Associated with Lower Prevalence of Type-2 Diabetes Mellitus in Raica Community of Rajasthan, India - Jain, Mili; Vyas, Raj Kumar (Disease and Health Research: New Insights Vol. 4, 2024)
Objective: This study was conceptualized to assess genotypic factors associated with a lower prevalence of type-2 diabetes mellitus in the Raica community of Rajasthan, India. Background: The prevalence of diabetes mellitus varies in different geographical regions, ethnic groups, and age groups. Lifestyle factors like sedentary life, smoking, obesity, and dietary factors. Materials and Methods: In this study, 114 people from the Raica community and 150 people from the non-Raica community were recruited. Their demographic details age and sex, anthropometric data body mass index, and waist-to-hip ratio, and laboratory parameters like fasting blood glucose, HbA1c and physiological parameters systolic and diastolic blood pressure were taken into consideration. Results: In the present study, there were 40 females and 74 males from the Raica community and, 52 females and 98 males from the non-Raica community. The mean age was 41.14 and 46.93 in Raica and non-Raica communities. The fasting blood glucose, HbA1c levels and physiological parameters were significantly lower in the Raica community (p< 0.05). The AG allele of the ARNT gene was more frequently seen in individuals with lower fasting blood glucose and no individual studied, had the AA allele. The distribution of ARNT G1511A genotype and allele type in subjects of Raica and Non-Raica communities with fasting blood sugar was compared. In the Raica community, 97.5% of subjects had fasting blood sugar levels below 126 mg/dl compared to non-Raica where only 38.6% of individuals had a fasting blood sugar below 126 mg/dl. Conclusion: In individuals with or without diabetes, the genetic variant under investigation has the same frequency of distribution in both Raica and non-Raica populations. One major contributing cause to the decreased prevalence of diabetes mellitus in the Raica community is thought to be their leanness and improved glucose regulation. The socio-economic and occupational environment of the members, which need to be explored further along with the genetic factors, may better account for the leanness and better control over the glucose levels in the Raica community.